2014
DOI: 10.1038/cddis.2014.388
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional repression of CDKN2D by PML/RARα contributes to the altered proliferation and differentiation block of acute promyelocytic leukemia cells

Abstract: Cell proliferation and differentiation are highly coordinated processes. These two processes are disrupted during leukemogenesis, resulting in differentiation block and uncontrolled proliferation in leukemia. To understand the mechanisms disrupting the coordination between the two processes in acute promyelocytic leukemia (APL), we investigated the regulatory mechanism of the negative cell cycle regulator CDKN2D by the promyelocytic leukemia/retinoic acid receptor α (PML/RARα) fusion protein and the role of CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 40 publications
4
25
0
1
Order By: Relevance
“…Previous studies have showed that RARα is a key player in the regulatory network of cell proliferation and differentiation [35,36]. Our current data suggested that CRC cell survival, proliferation, and colony formation were decreased by RARα knockdown, and were increased by RARα overexpression, suggesting that RARα plays an important role in the progression of CRC.…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies have showed that RARα is a key player in the regulatory network of cell proliferation and differentiation [35,36]. Our current data suggested that CRC cell survival, proliferation, and colony formation were decreased by RARα knockdown, and were increased by RARα overexpression, suggesting that RARα plays an important role in the progression of CRC.…”
Section: Discussionsupporting
confidence: 60%
“…The prolifer-and validated their differential expression using qRT-PCR. As shown in Figure 3E and Supplemental Table 1 (supplemental material available online with this article; doi:10.1172/JCI87880DS1), the expression levels of Cd74, Sod2, Ccl2, Bop1, Cdkn2d, and Ran mRNA, which are involved in cell-cycle regulation, survival, and proliferation (24)(25)(26)(27)(28), were decreased in NFAT5-deficient RAW 264.7 cells when compared with levels in control vector-transfected cells. In contrast, the expression levels of Dap3, Fas, Stk3, and Tiam1 mRNA, which promote apoptotic death (13,(29)(30)(31), were increased in the same cells.…”
Section: Resultsmentioning
confidence: 93%
“…The MigR1 vector (Addgene) was used to transduce NB4 cells for PU.1 overexpression. The preparation of retroviruses and transduction was done as previously described [ 45 ]. Briefly, the MigR1-PU.1 vector and the envelope plasmids were co-transfected into HEK-293T cells.…”
Section: Methodsmentioning
confidence: 99%